Valuing nutrients in soil and water: concepts and techniques with examples from IWMI studies in the developing world - Drechsel, Pay; Giordano, Mark; Gyiele, Lucy (International Water Management Institute, 2004)
Despite the importance of nutrient-water interactions, they are often ignored in analysis. After discussing the interrelationships between soil nutrients and water and reviewing methods for determining nutrient balances, this report describes an array of available methods for soil nutrient valuation and provides a discussion of four nutrient valuation studies, which together cover a range of scales, perspectives, and geographic contexts. It also includes case studies from Ghana, Mexico, Sub-Saharan Africa, and an examination of possible approaches to valuing soil organic matter and its various functions?an often ignored area in literature